Immune activation of the p75 neurotrophin receptor: implications in neuroinflammation - Danelon, Victor; Garret-Thomson, Sarah C.; Almo, Steven C.; Lee, Francis S.; Hempstead, Barbara L. (Frontiers in Molecular Neuroscience, 2023)
Despite structural similarity with other tumor necrosis factor receptor superfamily (TNFRSF) members, the p75 neurotrophin receptor (p75NTR, TNFR16) mediates pleiotropic biological functions not shared with other TNFRs. The high level of p75NTR expression in the nervous system instead of immune cells, its utilization of co-receptors, and its interaction with soluble dimeric, rather than soluble or cell-tethered trimeric ligands are all characteristics which distinguish it from most other TNFRs. Here, we compare these attributes to other members of the TNFR superfamily. In addition, we describe the recent evolutionary adaptation in B7-1 (CD80), an immunoglobulin (Ig) superfamily member, which allows engagement to neuronally-expressed p75NTR. B7-1-mediated binding to p75NTR occurs in humans and other primates, but not lower mammals due to specific sequence changes that evolved recently in primate B7-1. This discovery highlights an additional mechanism by which p75NTR can respond to inflammatory cues and trigger synaptic elimination in the brain through engagement of B7-1, which was considered to be immune-restricted. These observations suggest p75NTR does share commonality with other immune co-modulatory TNFR family members, by responding to immunoregulatory cues. The evolution of primate B7-1 to bind and elicit p75NTR-mediated effects on neuronal morphology and function are discussed in relationship to immune-driven modulation of synaptic actions during injury or inflammation.